[tex] \boxed{(x - a)(x - b) = 0}[/tex]
The equation above is the intercept form. Both a-term and b-term are the roots of equation.
[tex]x = - \frac{1}{3} \\ x = 5[/tex]
These are the roots of equation. Therefore we substitute a = - 1/3 and b = 5 in the equation.
[tex](x + \frac{1}{3} )(x - 5) = 0[/tex]
Here we can convert the expression x+1/3 to this.
[tex]x + \frac{1}{3} = 0 \\ 3x + 1 = 0[/tex]
Rewrite the equation.
[tex](3x + 1)(x - 5) = 0[/tex]
Simplify by multiplying both expressions.
[tex]3 {x}^{2} - 15x + x - 5 = 0 \\ 3 {x}^{2} - 14x - 5 = 0[/tex]
Answer Check
Substitute the given roots in the equation.
[tex]3 {(5)}^{2} - 14(5) - 5 = 0 \\ 75 - 70 - 5 = 0 \\ 75 - 75 = 0 \\ 0 = 0[/tex]
[tex]3( - \frac{1}{3} )^{2} - 14( - \frac{1}{3}) - 5 = 0 \\ 3( \frac{1}{9} ) + \frac{14}{3} - 5 = 0 \\ \frac{1}{3} + \frac{14}{3} - \frac{15}{3} = 0 \\ \frac{15}{3} - \frac{15}{3} = 0 \\ 0 = 0[/tex]
The equation is true for both roots.
Answer
[tex] \large \boxed {3 {x}^{2} - 14x - 5 = 0}[/tex]